2024
DOI: 10.3390/en17020511
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Optimal PV Allocation in a Distribution Network Using Evolutionary Algorithms

Wenlei Bai,
Wen Zhang,
Richard Allmendinger
et al.

Abstract: The growing distributed energy resource (DER) penetration into distribution networks, such as through residential and commercial photovoltaics (PV), has emerged through a transition from passive to active networks, which takes the complexity of planning and operations to the next level. Optimal PV allocation (sizing and location) is challenging because it involves mixed-integer non-linear programming with three-phase non-linear unbalanced power flow equations. Meta-heuristic algorithms have proven their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In [10], a novel iterative distflow model was proposed to address the imprecise problem for the traditional distflow model in DG planning. In [11], multiple evolutionary algorithms were used to solve the non-linear allocation problem of solar power, such as particle swarm optimization and artificial bee colony. The results showed that particle swarm optimization can provide a relatively robust and efficient means of maximizing the penetration of solar power, while artificial bee colony showed better performance in minimizing the voltage deviation.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], a novel iterative distflow model was proposed to address the imprecise problem for the traditional distflow model in DG planning. In [11], multiple evolutionary algorithms were used to solve the non-linear allocation problem of solar power, such as particle swarm optimization and artificial bee colony. The results showed that particle swarm optimization can provide a relatively robust and efficient means of maximizing the penetration of solar power, while artificial bee colony showed better performance in minimizing the voltage deviation.…”
Section: Introductionmentioning
confidence: 99%